Microsatellite instability is associated with reduced disease specific survival in stage III colon cancer. Issue 11 (November 2016) - Mohan, H.M.; Ryan, E.; Balasubramanian, I.; Kennelly, R.; Geraghty, R.; Sclafani, F.; Fennelly, D.; McDermott, R.; Ryan, E.J.; O'Donoghue, D.; Hyland, J.M.P.; Martin, S.T.; et al.
Abstract: Background: Up to 15% of colorectal cancers exhibit microsatellite instability (MSI), where errors in replication go unchecked due to defects in the mismatch repair system. This study aimed to determine survival in a large single-centre series of 1250 consecutive colorectal cancers subjected to universal MSI testing. Methods: Clinical and pathological features of patients with colorectal cancer identified on prospectively maintained colorectal and pathology databases at St. Vincent's University Hospital from 2004 to May 2012 were examined. Mismatch repair (MMR) status was determined by immunohistochemistry. Kaplan–Meier curves, the log-rank test and Cox regression were used to associate survival with clinical and pathological characteristics. Results: Of the 1250 colorectal cancers in the study period, 11% exhibited MSI (n = 138). Patients with MSI tumours had significantly lower rates of lymph node and distant metastases (MSI N+ rate: 24.8% compared with MSS N+ rate: 46.2%, p < 0.001). For Stage I and II disease MSI was associated with improved disease free survival (DSS) compared with MSS colon cancer. However, patients with Stage III MSI colon cancers had a worse DSS than those with MSS tumours. Stage III MSI tumours exhibited higher rates of lymphovascular invasion and perineural invasion than Stage I/II MSI tumours. Conclusion: MSI is associated with a reduced risk of nodal and distant metastases, with an improved DSS in Stage I/II colon cancer. However, when MSI tumours progress to Stage III these patients had worse outcomes and pathological features. New strategies for this cohort of patients may be required to improve outcomes.